A Partnership-Based Environmental Communication Model for Reducing Pollution in the Coastal Areas - Dony Arung Triantoro; Triyanto Triyanto (Komunikasiana: Journal of Communication Studies, 2025)
This study aims to analyze the partnership-based environmental communication model implemented by the Green Agent Student Activity Unit (UKM GA) at UTU to reduce pollution in coastal areas. Using a qualitative approach and data collected through interviews, the research identifies two dimensions of partnership-based environmental communication: internal and external partnerships. Internal partnerships are built through bonding and bridging social capital. Bonding social capital is reflected in members’ sense of solidarity and personal commitment to environmental cleanliness, while bridging social capital is realized through collaborations with other units within UTU. External partnerships are developed through linking social capital, evident in cooperation with communities outside UTU. The findings indicate that such partnerships not only expand social networks and enhance the legitimacy of environmental movements but also strengthen the community’s capacity to undertake collective actions to reduce pollution in coastal areas.